Advancements in Precision Medicine: Transforming the Landscape of Healthcare - Laudari, Shankar (Journal of National Heart and Lung Society Nepal, 2023)
Precision medicine has emerged as a revolutionary approach to patient care, tailoring treatment strategies based on individual traits, including genetic, environmental, and lifestyle factors. This editorial aims to highlight how advancements in precision medicine have the potential to transform the healthcare landscape, leading to more personalized and effective therapies.